The Future of Corruption’s Handling in the Regions and The Application of Restorative Justice - N. G. A. N. Ajeng Saraswati; Muhammad Rustamaji (Pandecta Research Law Journal, 2023)
Corruption is the biggest obstacle in implementing the development process, and until now, it has yet to be appropriately resolved although various models of retributive punishment have been applied. As a result, tThe losses suffered by the state continue to increase, and as a consequence, people cannot enjoy public facilities as they should. Cooperation between the Police, the Attorney General’s Office, and the Ministry of Home Affairs, which forms coordination between Aparat Pengawas Intern Pemerintah (APIP) and Aparat Penegak Hukum (APH), is a way to prevent corruption at the local government level. Criminal sanctions and imprisonment are no longer the main options for the government to deal with corruption problems in the regions. This choice then raises the pros and cons of the people who so far only recognize the existence of retributive justice as a form of criminal sanction. This study was made using the theory of consequentialism from Jeremy Bentham, and the Restorative Justice Theory put forward by John Braithwaite to provide an overview of the solutions used by APIP in preventing corruption in the regions. The doctrinal research method with a statutory approach will show the impact of the application of restorative justice on corruption practices in the regions. From this study, it can be seen that the restorative justice used by APIP can minimize losses suffered by the state and, at the same time, provide a deterrent effect for perpetrators of corruption.